2021
DOI: 10.1159/000512597
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Mild Cognitive Impairment among Chinese People: A Meta-Analysis

Abstract: <b><i>Background:</i></b> Mild cognitive impairment (MCI) induced the majority number of dementia patients. The prevalence of MCI in China varied across studies with different screening tools and diagnostic criteria. <b><i>Objective:</i></b> A systematic review and meta-analysis was conducted to estimate the pooled MCI prevalence among the population aged 55 years and older in China. <b><i>Methods:</i></b> PubMed, EMBASE, CNKI, Wanfang, CQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 42 publications
3
42
0
Order By: Relevance
“…Currently, a meta-analysis revealed that the prevalence rate of MCI is 15.4% in people aged >65 years, and 11.1% (95% confidence interval: 9.1–13.3%) in those aged 60–69 years in China ( Deng et al, 2021 ). The retired nurses not only had a higher proportion of MCI than controls in this study, but they also showed a higher proportion of MCI than some population-based surveys, even they were younger (mean age: 65.4 ± 8.0 years).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a meta-analysis revealed that the prevalence rate of MCI is 15.4% in people aged >65 years, and 11.1% (95% confidence interval: 9.1–13.3%) in those aged 60–69 years in China ( Deng et al, 2021 ). The retired nurses not only had a higher proportion of MCI than controls in this study, but they also showed a higher proportion of MCI than some population-based surveys, even they were younger (mean age: 65.4 ± 8.0 years).…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that poor compliance and improper use of inhalation devices often occurred in the older adults with low educational levels, which may also cause poor asthma control in the older adults [ 18 ]. Of course, cognitive impairment and dementia can decrease compliance, and the prevalence of cognitive impairment increases with age in Chinese [ 19 , 20 ], as in other populations. Access to inhalation devices can also affect compliance.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, according to metaanalysis based studies conducted in China, the prevalence of CI has increased rapidly from 8.5 to 21.8% in the last 20 years in that country. Physical inactivity was identified as one of the reasons for this (Deng et al, 2021). Furthermore, review studies concluded that certain medical conditions, including hypertension, obesity and diabetes, are associated with increased risk of dementia (Biessels et al, 2006;Sharp et al, 2011).…”
Section: Discussionmentioning
confidence: 99%